PENGARUH KETAATAN AKUNTANSI DAN PERILAKU TIDAK ETIS TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DENGAN PENGENDALIAN INTERNAL SEBAGAI VARIABEL PEMODERASI PADA KANTOR INSPEKTORAT KOTA LHOKSEUMAWE - Andirfa, Mulia; irfan; maryana; Putri Novianti (JAKTABANGUN: Jurnal Akuntansi & Pembangunan, 2022)
The problem of budget abuse in Lhokseumawe City leads to a tendency for accounting fraud where the Inspectorate as the regional financial supervisor has shown an attitude of lack of accounting compliance in the presentation of regional financial statements, this is shown due to negligence made by employees, especially in the audit section. Employee behavior also shows unethical behavior within the organization, where the impression is that the Inspectorate's employees let the regional financial cash into the company's personal account in Lhokseumawe City. If cash can be deposited into a personal account of the company or SKPD, this has proven that the performance of the Lhokseumawe City Inspectorate still needs internal control within the organization, with the aim of making improvements, enhancements, and strengthening the role of being supervisors, examiners and early warning providers to the system. reliable internal control and financial governance of the Regional Government (Pemda). Therefore, this study aims to determine the effect of accounting compliance and unethical behavior on the tendency of accounting fraud with internal control as a moderating variable at the lhokseumawe city inspectorate office.